Viral Vectors for the in Vivo Delivery of CRISPR Components: Advances and Challenges - Asmamaw Mengstie, Misganaw (Frontiers in Bioengineering and Biotechnology, 2022)
The Clustered Regularly Interspaced Short Palindromic Repeat (CRISPR) and its accompanying protein (Cas9) are now the most effective, efficient, and precise genome editing techniques. Two essential components of the CRISPR/Cas9 system are guide RNA (gRNA) and CRISPR-associated (Cas9) proteins. Choosing and implementing safe and effective delivery systems in the therapeutic application of CRISPR/Cas9 has proven to be a significant problem. For in vivo CRISPR/Cas9 delivery, viral vectors are the natural specialists. Due to their higher delivery effectiveness than other delivery methods, vectors such as adenoviral vectors (AdVs), adeno-associated viruses (AAVs), and lentivirus vectors (LVs) are now commonly employed as delivery methods. This review thoroughly examined recent achievements in using a variety of viral vectors as a means of CRISPR/Cas9 delivery, as well as the benefits and limitations of each viral vector. Future thoughts for overcoming the current restrictions and adapting the technology are also discussed.